Metabolic Profiling of a CB2 Agonist, AM9338, Using LC-MS and Microcoil-NMR: Identification of a Novel Dihydroxy Adamantyl Metabolite - Honrao, Chandrashekhar; Ma, Xiaoyu; Kulkarni, Shashank; Joshi, Vinit; Malamas, Michael; Zvonok, Alexander; Wood, JodiAnne; Kautz, Roger A.; Strand, David; Guo, Jason J.; Makriyannis, Alexandros (Frontiers in Pharmacology, 2020)
Adamantyl groups are key structural subunit commonly used in many marketed drugs targeting diseases ranging from viral infections to neurological disorders. The metabolic disposition of adamantyl compounds has been mostly studied using LC-MS based approaches. However, metabolite quantities isolated from biological preparations are often insufficient for unambiguous structural characterization by NMR. In this work, we utilized microcoil NMR in conjunction with LC-MS to characterize liver microsomal metabolites of an adamantyl based CB2 agonist AM9338, 1-(3-(1H-1,2,3-triazol-1-yl) propyl)-N-(adamantan-1-yl)-1H-indazole-3-carboxamide, a candidate compound for potential multiple sclerosis treatment. We have identified a total of 9 oxidative metabolites of AM9338 whereas mono- or di-hydroxylation of the adamantyl moiety is the primary metabolic pathway. While it is generally believed that the tertiary adamantyl carbons are the preferred sites of CYP450 oxidation, both the mono- and di-hydroxyl metabolites of AM9338 show that the primary oxidative sites are located on the secondary adamantyl carbons. To our knowledge this di-hydroxylated metabolite is a novel adamantyl metabolite that has not been reported before. Further, the stereochemistry of both mono- and di-hydroxyl adamantyl metabolites has been determined using NOE correlations. Furthermore, docking of AM9338 into the CYP3A4 metabolic enzyme corroborates with our experimental findings, and the modelling results also provide a possible mechanism for the unusual susceptibility of adamantyl secondary carbons to metabolic oxidations. The novel dihydroxylated AM9338 metabolite identified in this study, along with the previously known adamantyl metabolites, gives a more complete picture of the metabolic disposition for adamantyl compounds.